Blind man's bluff: The ethics of quantity surcharges - Gupta, Omprakash K. (Journal of business ethics, 1996)
Empirical evidence, including a recent field study in Northwest Indiana, indicates that supermarkets and other retail merchants frequently incorporate quantity surcharges in their product pricing strategy. Retailers impose surcharges by charging higher unit prices for products packaged in a larger quantity than smaller quantity of the same goods and brand. The purpose of this article is to examine the business ethics of such pricing strategy in light of empirical findings, existing government regulations, factors that motivate quantity surcharges and prevailing consumer perceptions.